Teacher training for PhD students and new faculty in economics. Issue 2 (3rd April 2018) - Allgood, Sam; Hoyt, Gail; McGoldrick, KimMarie
ABSTRACT: Past studies suggest that a majority of economics graduate students engage in teaching-related activities during graduate school and many go on to academic positions afterwards. However, not all graduate students are formally prepared to teach while in graduate school nor are they fully prepared to teach in their first academic position. The authors characterize current teaching experience and training of graduate students from the point of view of directors of graduate studies and of newly minted academic economists. The authors also query department chairs and new faculty about teacher training, support available for new faculty, and the degree to which newly hired Ph.D. economists are prepared to teach. Findings indicate that while some training is available, there is room for enhancing teacher training in economics.